Língua, cultura e identidade no discurso educativo de e para Suábios do Danúbio em Entre Rios/Paraná: análises e propostas de leitura - Socoloski, Adriana (2021)
The present research takes as an object of study the educational process of Colégio Imperatriz Dona Leopoldina, located in the District of the Municipality of Guarapuava, Midwest region of the State of Paraná, founded by a group of immigrants of multiple European origins, called Swabians of the Danube. The general objective of this research consists of presenting proposals for readings that make it possible language concepts, culture and identity that permeate educational discourses related to immigrant communities, in particular, from the immigration of the Danube Swabians. As for the specific objectives , it is intended to identify cultural, linguistic and identity characteristics in the most diverse discourses that permeate the colony and its educational reality; Create a state of the art by portraying the educational historical process of Colégio Imperatriz; create a state of the art by portraying the educational historical process of Colégio Imperatriz; analyze the main official documents that govern Brazilian education today, in order to compare ethnic and regular schools with regard to the adaptation and socialization of students and the preservation of their language and culture.Theoretically, the research is anchored in Orlandi (1995), Pêcheux (1999), Barzotto (2014), Puh (2017), and among other authors who discuss discourse analysis and the de-writing process (BARZOTTO, 2014). The corpus is divided into two groups: the first brings together academic productions that portray the educational process of Colégio Imperatriz; the second addresses the main official documents that guide national education today. In this way, new possibilities will be explored in order to provide analyzes and readings that would spread other perspectives on the way a national project is constituted, which takes into account ethnic and cultural differences as elements that form a fundamental process for any nation in contemporary times. Finally, a current panorama of Colégio Imperatriz Dona Leopoldina is outlined, with the intention of leading the reader to understand the changes that have taken place, over the years, in this institution, allowing a reflection on the governmental changes regarding education offered to students. immigrants, in order to highlight the main differences between the education offered by ethnic and non-ethnic institutions.